MENINGKATKAN KEMAMPUAN MEMAHAMI BACAAN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TURNAMENT (TGT) PADA SISWA KELAS IV SDN 010 LANGGINI - Ulfa Ramadhani; Zariul Antosa (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is motivated by the low ability of grade IV SDN 010 Langgini students to understand reading, out of 18 students there are 4 (22%) good people, 1 (6%) enough people, 4 (22%) less people and 9 (50%) ) people are very lacking. This research is a Class Action Research (CAR) which aims to improve the reading comprehension of Grade IV students at SDN 010 Langgini through cooperative learning models of team game tournament. This research was conducted in the even semester of the 2018/2019 school year for 2 weeks on January 14-28, 2019. The research subjects were Grade IV students of SDN 010 Langgni, as many as 18 students, consisting of 6 men and 12 women. The study was conducted in two cycles, each cycle consisting of four stages namely planning, implementing, observing and reflecting during the learning process using cooperative learning models of teams game tournament. Research results obtained before the action 45.3 and increased in cycle I as much as 56.9% with an average of 71.1 and increased again in the second cycle as much as 81.4% of the base score with an average of 82.2. based on the results of these improvements prove that the cooperative learning model team game tournament can improve the ability of fourth grade students SDN 010 Langgini in understanding reading